2013
DOI: 10.1186/1751-0147-55-35
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography imaging of a leopard tortoise (Geochelone pardalis pardalis) with confirmed pulmonary fibrosis: a case report

Abstract: An approximately 20-year-old, female Leopard tortoise (Geochelone pardalis pardalis) was presented with dypsnea, wheezing, anorexia and depression. Whole body radiographs revealed generalized diffuse unstructured ‘interstitial lung pattern’ with thickened pulmonary septae while computed tomography (CT) showed emphysematous lung parenchyma and thickened pulmonary septae bordered by irregular ground-glass opacity with smaller areas of ‘honeycombing’. These imaging findings together with histopathologic findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Pulmonary fibrosis is a chronic and progressive interstitial lung disease, in veterinary medicine, the diagnosis of pulmonary fibrosis is made based on clinical findings, imaging diagnosis and exclusion of other cardiorespiratory diseases. However, the definitive diagnosis requires histopathological examination (LIM et al, 2013). Due to the fact that the animal's guardian does not authorize procedures that would histopathologically confirm the pulmonary fibrosis condition, here we only raise insights regarding a clinical protocol used in indicative tomography images.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Pulmonary fibrosis is a chronic and progressive interstitial lung disease, in veterinary medicine, the diagnosis of pulmonary fibrosis is made based on clinical findings, imaging diagnosis and exclusion of other cardiorespiratory diseases. However, the definitive diagnosis requires histopathological examination (LIM et al, 2013). Due to the fact that the animal's guardian does not authorize procedures that would histopathologically confirm the pulmonary fibrosis condition, here we only raise insights regarding a clinical protocol used in indicative tomography images.…”
Section: Resultsmentioning
confidence: 98%
“…These reports raised the suspicion of GI hypomotility, a Coelomic Cavity Tomography (CT) was requested, Metoclopramide 1 mg/Kg/IM/SID was administered and hydration baths were performed with warm water. Due to the suspicion of pulmonary fibrosis being something not reported in the chelonian medical clinic, a search in the bibliography was carried out and only a single case in terrestrial chelonians was found (LIM et al, 2013), a Leopard Tortoise (Stigmochelys pardalis) that the tomography showed emphysematous lung parenchyma and thickened lung septa, bordered by irregular ground-glass opacity, but the animal in the report was euthanized and there were no other reports in the literature regarding pulmonary fibrosis in chelonians, nor information about therapeutic protocols. Based on the authors' clinical experience and on the therapeutic protocols that constitute corticosteroids as the therapy for idiopathic pulmonary fibrosis, a therapeutic protocol was instituted with Lactulone 0.5ml/KG/PO -7 days for the presented hepatic steatosis, Aminophylline 2 Mg/KG/IM every 48 hours 5 applications, Dexamethasone 0.2 Mg/Kg/IM (CARPENTER, 2018) every 48 hours for 7 applications and tube feeding.…”
Section: Resultsmentioning
confidence: 99%
“…CT is the safest and most sensitive method for diagnosing pathology of bones and soft tissue in chelonians (Wyneken 2014). The method also allows multiplanar reconstruction and threedimensional images of organs and tissues inside the coelom of chelonians (Bonelli et al 2013;Lim et al 2013;Mans et al 2013;Wyneken 2014).…”
mentioning
confidence: 99%